Resposta afetiva no exercício intervalado de alta intensidade em homens fisicamente ativos e insuficientemente ativos - Frazão, Danniel Thiago (2016)
Introduction: Affective response (feeling of pleasure/displeasure) during exercise has impact on future physical activity participation. Despite the physiological benefits of high-intensity interval exercise (HIIE), little is known on affective response during this exercise, mainly in individuals with different physical activity status. Objective: To analyze the affective response during a bout of HIIE in physically and insufficiently active men. Methods: Fifty-eight men (aged 25.3 ± 3.6 years) volunteered to participate of this study: i) active (n = 29) and ii) insufficiently active (n = 29). Each individual undertook the following procedures: i) initial screening and physical evaluation, ii) maximal exercise test, and iii) a bout of HIIE. The HIIE protocol consisted of 10 x 60s work bouts at 90% of maximal treadmill velocity (MTV) interspersed with 60s of active recovery at 30% of MTV. Affective response (Feeling Scale, -5/+5), rating of perceived exertion (Borg’s RPE, 6-20), and heart rate (HR) were recorded during the last 10s of each work bout. A two-factor mixed-model ANOVA, groups x work bouts, with repeated measures in the second factor, independent-samples t test, chi-squared test, and Pearson’s product-moment correlation were used to data analysis. Results: Insufficiently active group displayed lower affective response over time (work bout 4 to 10) than the active group (p<0.05). The insufficiently active group displayed lower values of mean, lowest, and highest affective response, as well as lower values of affective response at the highest RPE than the active group (p<0.05). Moreover, 37.9% and 84.8% of insufficiently active and active groups, respectively, reported the HIIE as unpleasant (p<0.05). There were no differences in the RPE and HR between the groups (p>0.05). There was a negative correlation between RPE and affective response in the active (r = -0.74) and insufficiently active (r = -0.51) groups. Conclusions: The physical activity status influences the affective response during HIIE. Insufficiently active men report less pleasure/more displeasure during HIIE compared to the active men. Independent of physical activity status, individuals who perceive the HIIE harder report lower affective response.